Isolated Knee Osteonecrosis Secondary to Corticosteroid Use in Two Patients with Idiopathic Thrombocytopenic Purpura - YAĞCI, İLKER (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2010)
Idiopathic thrombocytopenic purpura (ITP) is characterized by low platelet count and mucocutaneous bleeding and steroids are commonly used for the treatment of this disorder. Osteonecrosis is one of the well-known side effects of steroids. However, no case of isolated knee osteonecrosis after steroid use has been reported in the literature to date. In this paper, we presented two cases of knee osteonecrosis who had received steroids for the treatment of ITP. Turk J Phys Med Rehab 2010;56:94-6.
Keywords: Knee osteonecrosis; avascular necrosis; idiopathic thrombocytopenic purpura; steroid